Spatial agglomeration and product market competition - Christoph Alsleben (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2005)
This paper tests the hypothesis that product market competition has a negative impact on spatial agglomeration. This hypothesis emerges as an interpetation of the models by Combes and Duranton (2001) and Alsleben (2005) which are about firms' location choice in the presence of knowledge spillovers. Using data for German manufacturing industries, the result is that, while controlling for other agglomeration forces, higher industrial concentration, measured by the Herfindahl index of concentration of sales, implies stronger spatial agglomeration, as measured by Ellison and Glaeser's (1997) index of concentration.
Keywords: 330